Business Success Development among Female Entrepreneurship in Bangkok - Thanaphansin, Nattawat; Wichitsathian, Sareeya (MBA-KKU Journal, 2026)
The purposes of this study are to: 1) examine the characteristics of female entrepreneurship in business operations, 2) investigate the skills of female entrepreneurs that contribute to business success, and 3) propose guidelines for developing business success among female entrepreneurs. This study employed a qualitative research design. Data were collected through a review of relevant documents and in-depth interviews with 10 female entrepreneurs who had successfully operated their businesses for at least 10 years. The findings revealed that the characteristics of female entrepreneurs in business operations were shaped by the development of business ideas and strategies from the initial stage of entrepreneurship to long-term success, reflecting the authentic identities of the entrepreneurs themselves. In addition, the skills that promote business success were associated with the unique strengths and diversity of women, which influenced business operations in several aspects, including communication, negotiation, creativity, and sincerity.These qualities contributed to the development of business success among female entrepreneurs through opportunity recognition, risk awareness, and continuous self-development.